Project scheduling handbook - Hutchings, Jonathan F. (Civil and environmental engineering, 2004)
Offering real-world strategies gleaned from years of professional experience, this book contains the essential tools to prepare a well-organized, efficient, and effective working production schedule for successful construction outcomes. The only guide to address the day-to-day needs with hands-on, problem-resolution strategies, the book views the industry from an insider's perspective and depicts the integral role of a project scheduler in the design of lucrative schemes and layouts for contemporary residential, commercial, industrial, and civil construction ventures. It conveys skills for pro.